Maize genetic improvement for enhanced productivity gains in West and Central Africa - Ajala, S.; Badu-Apraku, Baffour; Menkir, A. (2012)
During the past 45 years, the genetic improvement programs of IITA and its partners have made spectacular progress in developing high-yielding crop varieties that offered best-bet solutions to major production constraints, such as, cassava mosaic, maize streak, Striga, soybean rust, insect pests, and even drought. These have led to dramatic increases in the production of cassava, maize, soybean, cowpea, and yam in sub-Saharan Africa that have directly contributed to increases in food availability and indirectly to improvements in national economies. This section presents the status, progress, and achievements, and also outlines future work on crop improvement by genetic enhancement in IITA's six crops.